‘Work with me’: implicature in speech by Tun Abdullah Ahmad Badawi - Yaakub, Yusniza; Halim, Rohizah; Abdul Mutalib, Mashetoh (Universiti Malaysia Perlis, 2017)
Political speeches is an avenue for leaders to communicate their ideology with the people that they lead. Through language, leaders attained and exercised power and also gained public approval for future actions. The components of a successful speech include a combination of explicit and implicit language. And in certain situations, what is implied can have even more impact to the audience. Indirect speech or implicature is a area of study in pragmatics that deals with the relationship between language, culture and society. This paper analyses the relationship between the use of implicatures, the speaker and circumstances surrounding the production of political speeches. Using Gricean theory on implicature (1975) that has been adapted to Asmah’s implicature framework on indirect speech acts, the study examines three speeches made by Tun Abdullah Ahmad Badawi at the opening ceremony of the UMNO general assembly. The findings show that Tun Abdullah’s language use took the audience and Malay culture into account. His usage of implicatures also helped to accentuate his particular brand of leadership